Five Questions about Mycoviruses - Son, Moonil; Yu, Jisuk; Kim, Kook-Hyung (PLoS pathogens, 2015)
According to the most recent report concerning virus taxonomy, the genome of most mycoviruses consists of double-stranded RNA (dsRNA), while the genome of about 30% of mycoviruses is composed of a positive, single-stranded RNA (+ssRNA) [2]. [...]Sclerotinia scerotiorum RNA virus L is closely related to the human pathogen hepatitis E virus and rubi-like viruses [3]. Similar scenarios might also explain the origin of plant viruses; i.e., some plant viruses may have originated from mycoviruses that moved from fungus to plant [7]. Because convincing data are lacking, however, the origin of mycoviruses remains a mystery.